Bioremediation of Pb and Cd Metal from Inner Ambon Bay Sediment Which Contaminated With Heavy Metal Using Aspergillus niger - Male, Yusthinus T; Seumahu, Cecillia Anna; Malle, Dominggus (Indonesian Journal of Chemical Research, 2020)
Bioremediation is a method that use microorganism to extract heavy metal from contaminated waste. In this research Aspergillus niger was used to extract heavy metal such as Pb and Cd of marine sediment from Waiheru shore, Inner part of Ambon Bay, which was detected as significantly high heavy metal contaminated site among seven sites. Bioremediation were done using Aspergillus nigers to extract Pb and Cd metal from sediment, then their solubility being measured in filtrate media. Result shows that Cd metal were only detected 15 days after incubation while Pb were detected since the first day incubation. This result also showing the fluctuating solubility of Pb metal. It is suspected that this occurs due to biosorption ability of the fungi that being used which triggers metal accumulation in the cell structure. It is therefore can be concluded that Aspergillus niger can be used in bioremediation of sediment that are being contaminated by Pb and Cd heavy metals.